2019
DOI: 10.18632/oncotarget.27274
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transition of the blood-brain barrier in the development of non-small cell lung cancer brain metastases

Abstract: Invasion of the brain by non-small cell lung cancer (NSCLC) results in a shift of the blood-brain barrier (BBB) to the insufficiently characterized blood-tumor barrier (BTB). Effective drug delivery through the BTB is one of the greatest therapeutic obstacles in treating brain metastases. Using an experimental model, we defined key changes within the BTB and the BBB in the brain around the tumor (BAT) region over time. Brain-seeking NSCLC cells were delivered into the circulation of athymic-nude mice via intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…In fact, by using a BC mouse model, they demonstrated that the VEGF-receptor tyrosine kinase inhibitor PTK787/Z 222,584 significantly reduces CD31+ vessels in brain lesions, enhances apoptosis within the tumor mass, thereby decreasing the tumor burden in the brain [ 114 ]. This is in line with evidence showing that CD31 expression is often upregulated in endothelial cells of brain metastases of BCs, cervical carcinomas, and non-small cell lung cancers [ 115 , 116 ].…”
Section: Hallmarks Of Metastatic Bcmsupporting
confidence: 90%
“…In fact, by using a BC mouse model, they demonstrated that the VEGF-receptor tyrosine kinase inhibitor PTK787/Z 222,584 significantly reduces CD31+ vessels in brain lesions, enhances apoptosis within the tumor mass, thereby decreasing the tumor burden in the brain [ 114 ]. This is in line with evidence showing that CD31 expression is often upregulated in endothelial cells of brain metastases of BCs, cervical carcinomas, and non-small cell lung cancers [ 115 , 116 ].…”
Section: Hallmarks Of Metastatic Bcmsupporting
confidence: 90%
“…One of the major obstacles to the treatment of a brain tumor is the blood-brain barrier [ 44 ]. The transport analysis together with ex vivo, and in vivo data collectively provided multiple lines of evidence that the minimally invasive injection of CM is effective to deliver tumor-suppressing factors in the mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of healthy CNS vessels express PDGFR-β protein [43,44]. Expression of other pericyte proteins is generally dependent upon the developmental stage or pathology [45][46][47][48]. Göritz et al reported increased pericyte proliferation after spinal cord injury in a mouse model.…”
Section: Discussionmentioning
confidence: 99%